2015
DOI: 10.17795/bhs-27547
|View full text |Cite
|
Sign up to set email alerts
|

Bee Venom Induces Unfolded Protein Response in A172 Glioblastoma Cell Line

Abstract: Background: Glioblastoma is a type of brain tumor with poor response to available therapies, and shows high rate of mortality. Despite remarkable advancements in our knowledge about cytogenetic and pathophysiologic features of glioblastoma, current treatment strategies are mainly based on cytotoxic drugs; however, these therapeutic approaches are facing progressive failure because of the resistant nature of glioblastomas. In the recent years, however, promising results have emerged owing to targeted therapies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…4D and E). These observations support the idea that HSCL correspond to immature hematopoietic cells and unravel the activation of several stress pathways which have been shown to be misregulated in CML/AML LSCs, such as autophagy 48 , mitophagy 49 and UPR 50,51 .…”
Section: Hscl Cell Lines Exhibit a Molecular Signature Resembling Hspcsupporting
confidence: 84%
“…4D and E). These observations support the idea that HSCL correspond to immature hematopoietic cells and unravel the activation of several stress pathways which have been shown to be misregulated in CML/AML LSCs, such as autophagy 48 , mitophagy 49 and UPR 50,51 .…”
Section: Hscl Cell Lines Exhibit a Molecular Signature Resembling Hspcsupporting
confidence: 84%
“…Also, Fan et al described that the melittin gene-transfected human osteosarcoma cell line (MG63) triggered UPR-mediated apoptosis through a significant increase in the XBP1 and CHOP proteins level [ 24 ] . Bazi and colleagues also reported BV as an activator of the UPR pathway and UPR-related apoptosis in the A172 glioblastoma cell line [ 25 ] . While some investigations have reported that melittin restricts the proliferation and promotes apoptosis in colon cancer cells [ 12 , 29 ] , the autophagy and UPR pathways have not been targeted so far in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the BV and its main constituent melittin on the autophagy and UPR pathways have been reported in different cancers such as osteosarcoma [ 24 ] , glioblastoma [ 25 ] , lung [ 26 ] , liver [ 27 ] , and cervix cancers [ 28 ] . In spite of various investigations on the role of melittin in the growth inhibition and apoptosis induction in colon cancer cells [ 12 , 29 ] , to the best of our knowledge, there is no report about the function of melittin in autophagy and UPR pathways in the mentioned cells.…”
Section: Introductionmentioning
confidence: 99%
“…ROS are expected to be the ideal targets for therapeutic intervention, for high ROS levels are particularly relevant to BCR/ ABL kinase inhibitor resistance. [4,43] Antioxidants that regulate the level of oxidative stress are the primary defense line to regulate the overall state of health. Ivermectin is a new anti-cancer drug targeted to mitochondria, which can selectively kill CML cells by inducing oxidative stress and mitochondrial dysfunction, being a promising candidate drug for the treatment of CML.…”
Section: Traditional Treatment and Antioxidant Treatment For CMLmentioning
confidence: 99%
“…Therefore, researchers are actively looking for new drugs that can stimulate cell differentiation and induce apoptosis of acute leukemia and multiple myeloma cells. ROS are expected to be the ideal targets for therapeutic intervention, for high ROS levels are particularly relevant to BCR/ABL kinase inhibitor resistance [4,43] …”
Section: Traditional Treatment and Antioxidant Treatment In Different...mentioning
confidence: 99%